Perancangan Website “Agriverse” Media Informasi dan Edukasi Teknik Hidroponik Menggunakan Metode User Center Design - Nanda Wijaya Putra; Shinta Arafah Hidayanti; Evlyn Jane Putri; Andi Nurfitriana; Dany Fadhilah; Aditya Wicaksono; Hari Agung Adrianto (Jurnal Sains dan Teknologi, 2023)
As an innovation for food security in Indonesia, the Agriverse website has been developed, which is a platform for information media and education on hydroponic techniques. The website contains e-commerce services, agricultural extension services, data on nearby agricultural shops, articles and discussion forums. Because people still rarely know about hydroponic techniques, designing the website interface relies on the needs of target users using the User Centered Design method. Testing the Agriverse website using Black Box Testing and 5 Second Testing resulted in an average time of 9.6 seconds to try each feature, and the entire feature system for the website's functional requirements was successfully used.